2013
DOI: 10.1016/j.jcma.2012.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Klippel–Trenaunay syndrome in combination with congenital dislocation of the hip

Abstract: Klippel-Trenaunay syndrome (KTS) is a rare and sporadic disorder characterized by the triad of capillary malformations, venous varicosities, and limb hypertrophy. The clinical manifestations of KTS are heterogeneous. In this report, we present a unique case of KTS in combination with congenital dislocation of the hip (CDH) in a 4-day-old female neonate. The patient had a widespread port-wine stain surrounded by regions of unaffected skin in a mosaic pattern, cutaneous hemangioma on the upper lip, left-sided he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Deep vein abnormalities increase deep vein thrombosis risk, possibly leading to a pulmonary embolism [4,19,21]. Ancillary symptoms include cataracts, glaucoma, hip dislocation, blood clotting, cellulitis, lymphedema, internal bleeding, acrodactyly, syndactyly, polydactyly, congenital hip dislocation, peripheral neuropathy, metatarsal, and phalangeal agenesis to osteolysis, as well as larger cardiovascular, gastrointestinal, liver, spleen, and genitourinary tract problems [4,5,19,[22][23][24][25]. Additionally, the moderate psychomotor delay has been described in KTS and may be related to 2q27.3 microdeletion [26].…”
Section: Discussionmentioning
confidence: 99%
“…Deep vein abnormalities increase deep vein thrombosis risk, possibly leading to a pulmonary embolism [4,19,21]. Ancillary symptoms include cataracts, glaucoma, hip dislocation, blood clotting, cellulitis, lymphedema, internal bleeding, acrodactyly, syndactyly, polydactyly, congenital hip dislocation, peripheral neuropathy, metatarsal, and phalangeal agenesis to osteolysis, as well as larger cardiovascular, gastrointestinal, liver, spleen, and genitourinary tract problems [4,5,19,[22][23][24][25]. Additionally, the moderate psychomotor delay has been described in KTS and may be related to 2q27.3 microdeletion [26].…”
Section: Discussionmentioning
confidence: 99%
“…Although any part of the body can be involved, the most commonly affected sites are the lower extremities [7]. Limb findings varied from finger and toe deformities such as acrodactyly, polydactyly, syndactyly, metatarsal and phalangeal agenesis to osteolysis, congenital dislocation of the hip and peripheral neuropathy [2, 8]. As for vascular malformations, almost all organs of the body can be affected, including cardiovascular system, gastrointestinal tract, liver, spleen, and genitourinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…KTS was reported to associate with other congenital malformations, such as congenital dislocation of the hip (CDH) [8] and spinal arteriovenous malformation [11]. However, KTS may rarely occur in combination with kyphoscoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the exact inheritance of KTWS is unknown. It has been suggested that the disease is sporadic [209][210][211], but familial cases and a putative autosomal dominant model of inheritance were also considered [212][213][214]. The researchers have proposed AGGF1, a gene encoding a potent angiogenic factor, as a candidate gene for KTWS [215].…”
Section: Klippel-trénaunay-weber Syndromementioning
confidence: 99%